2021
DOI: 10.48550/arxiv.2105.03548
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamics of ramping bursts in a respiratory neuron model

Abstract: Intensive computational and theoretical work has led to the development of mutliple mathematical models for bursting in respiratory neurons in the pre-Bötzinger Complex (pre-BötC) of the mammalian brainstem. Nonetheless, these previous models have not captured the preinspiratory ramping aspects of these neurons' activity patterns, in which relatively slow tonic spiking gradually progresses to faster spiking and a full-blown burst, with a corresponding gradual development of an underlying plateau potential. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Our recent biophysical characterization of INaP for these neurons has confirmed that this current is slowly inactivating (Yamanishi et al, 2018), which is a basic assumption of the present and previous models , although the details of the voltage-dependent kinetic properties are more complex than represented by the first-order kinetics in the present and previous models. Moreover, some additional currents or dynamical processes (e.g., inhibitory currents from local circuit connections, synaptic depression) (Thoby- Hayes et al, 2008;Andrew and Del Negro, 2015;Phillips et al, 2018;Baertsch et al, 2018;Juárez-Vidales, et al, 2021;Abdulla et al, 2021;Revill et al, 2021), which are not considered in the model, may play a role in augmenting/shaping inspiratory bursting.…”
Section: Extensions and Limitations Of The Modelmentioning
confidence: 99%
“…Our recent biophysical characterization of INaP for these neurons has confirmed that this current is slowly inactivating (Yamanishi et al, 2018), which is a basic assumption of the present and previous models , although the details of the voltage-dependent kinetic properties are more complex than represented by the first-order kinetics in the present and previous models. Moreover, some additional currents or dynamical processes (e.g., inhibitory currents from local circuit connections, synaptic depression) (Thoby- Hayes et al, 2008;Andrew and Del Negro, 2015;Phillips et al, 2018;Baertsch et al, 2018;Juárez-Vidales, et al, 2021;Abdulla et al, 2021;Revill et al, 2021), which are not considered in the model, may play a role in augmenting/shaping inspiratory bursting.…”
Section: Extensions and Limitations Of The Modelmentioning
confidence: 99%